2014
DOI: 10.4085/1062-6050-49.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Induced Balance Impairment in Young Soccer Players

Abstract: Context: Although balance is generally recognized to be an important feature in ensuring good performance in soccer, its link with functional performance remains mostly unexplored, especially in young athletes.Objective: To investigate changes in balance induced by fatigue for unipedal and bipedal static stances in young soccer players.Design: Crossover study. Setting: Biomechanics laboratory and outdoor soccer field.Patients or Other Participants: Twenty-one male soccer players (age ¼ 14.5 6 0.2 years, height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 29 publications
3
56
0
5
Order By: Relevance
“…Change of direction ability in team sport 7 impairment which is a model of change of direction, especially in single leg stance (Pau, Ibba, & Attene, 2014). Lakomy and Haydon (2004) found also that, in multiple (<10) sprint trials, increased fatigue and slower sprint times occurred in enforced deceleration within 6 m after the finish line compared with sprints without forced deceleration (Lakomy & Haydon, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Change of direction ability in team sport 7 impairment which is a model of change of direction, especially in single leg stance (Pau, Ibba, & Attene, 2014). Lakomy and Haydon (2004) found also that, in multiple (<10) sprint trials, increased fatigue and slower sprint times occurred in enforced deceleration within 6 m after the finish line compared with sprints without forced deceleration (Lakomy & Haydon, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Quantitative analysis of postural sway, which is known to be related to postural control system performance, revealed that soccer players present superior balance abilities compared with basketball players, swimmers and non-athletes for single leg stance (Matsuda, Demura, & Uchiyama, 2008, while it has been suggested that poor postural control may represent a predictive factor for lateral ankle sprains (Beynnon, Murphy, & Alosa, 2002, Trojian & McKeag, 2006. Significant increases in sway, which indicate balance impairment, were also observed as the consequence of intense muscular effort made during a competitive match or repeated sprints (Brito et al, 2012;Pau, Ibba, & Attene, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…COP PL and Mean MV COP , see Chiari, Rocchi, & Cappello, 2002) were normalized by dividing their values by the participant's height. The proposed methodology was used in previous similar studies on elite soccer players or athletes of other disciplines and can be considered accurate and reliable (Hrysomallis, 2011;Matsuda et al, 2008;Pau et al, 2014). At the time of the test, players were called two at a time into a dedicated quiet room for measurements.…”
Section: Data Acquisition and Post-processingmentioning
confidence: 99%
“…In the elderly population, decline in balance control is a major risk factor for falls [3]. In sports, the standing limb in the kicking action in soccer and taekwondo is important to ensure stability needed for successful execution [25,35]. From an injury prevention perspective, balance deficit that occurs immediately after anaerobic stress and fatigue could affect sports performance and might increase the probability of injuries [29,32].…”
Section: Introductionmentioning
confidence: 99%